ANALYSIS OF LEGAL CERTAINTY, LEGAL PROTECTION AGAINST CANCELLATION OF REGISTERED MARKS (STUDY OF DECISION NUMBER 03/PDT.SUS-MEREK/2015/PN NIAGA MEDAN) - Lenny Mutiara Ambarita (RADJA PUBLIKA, 2023)
The purpose of this research is to analyze legal certainty and legal protection against cancellation of registered trademarks (Decision Study Number 03/Pdt.Sus-MEREK/2015/PN Niaga Medan). The type of research used in writing this thesis is normative juridical research. Normative juridical research,